Tetranychus urticae (Acari: Tetranychidae) on Gerbera jamesonii Bolus and Hook (Asteraceae) - EA. Silva; PR. Reis; TMB. Carvalho; BF. Altoé (Brazilian Journal of Biology)
Gerbera (Gerbera jamesonii Bolus and Hook,) is an ornamental Asteraceae of great commercial value, and pests can affect adversely its cultivation. More than 20 species of arthropods cause economic damage on gerbera, among them the two spotted mite, Tetranychus urticae Koch, 1836 (Acari: Tetranychidae), considered a key pest for this and other ornamental plants. In this work, some life-cycle aspects of T. urticae on gerbera, considered important for the knowledge of its population dynamics and for pest management programs, were studied. Mites were reared on 3-cm diameter arenas of gerbera leaf discs maintained on distilled water in Petri dishes, under laboratory conditions of 25 ºC, 70 ± 10% RU and 14-hour photophase, with only one egg left per arena, in a total of 262 arenas. Egg viability was 96.5% and 97.1% for unmated and mated females, respectively. Unmated females originated larvae which lived for 3.2 days and the stages of protonymph and deutonymph, 1.9 and 1.6 days, respectively; those from mated females lived 3.5 days and for protonymphs and deutonymphs, 2.0 and 1.6 days, respectively. Except for the duration of one generation (T), with similar values, 18.6 and 19.7 days, respectively for unmated and mated females, the net reproductive rate of increase (Rº), the innate capacity to increase in number (r m) and the finite rate of growth (λ) were different for mated and unmated females, respectively 11.5 and 24.6 for R0; 0.12 and 0.17 for r m and 1.13 and 1.19 for λ.